TARI TOGA DARI NAGARI SIGUNTUR DHARMASRAYA: EKSISTENSI DAN PELESTARIAN 1990–2022 - Naldi, Hendra; Syafrina, Yelda; Nengsi, Diana Putri; Erniwati, Erniwati (UI Scholars Hub, 2023)
This article report the study of traditional dance in Siguntur Dharmasraya, West Sumatra. Marhasnida, a cultural activist from Nagari Siguntur, created the toga dance. This article explains how the dance was created, developed, and performed from stage to stage and passed on to the younger generation for preservation. This historical research observed and analyzed the actions of an individual closely related to the development of toga dance. Data were obtained through observation, interviews, and tracing of personal archives pertaining to various aspects of the dance, including its history and movements. This research found (1) that Marhasnida has been involved in the preservation of toga dance since 1990; (2) that toga dance has been performed in various local, national, and international performances; and (3) that toga dance preservation involves educational institutions and students at the school where Marhasnida teaches, which also serves as a forum for fostering young dancers who will preserve the dance. Findings indicate that traditional activities are not only preserved and passed on to the millennials by formal institutions established by the government, but also by an individual who is also a local activist and culture expert. However, this study also shows that the involvement of formal institutions such as schools is quite effective for attracting young talents to preserve and practice regional arts. However, not all art activists are teachers and have access to formal education. For this reason, an educational curriculum that can stimulate actions to explore cultural values and local wisdom by providing flexibility for teachers to create, innovate, and collaborate with practitioners is a commendable measure.